Study on the Electrical and Mechanical Properties of TiC Particle-Reinforced Copper Matrix Composites Regulated by Different Rare Earth Elements - Denghui Li; Changfei Sun; Zhenjie Zhai; Zhe Wang; Cong Chen; Qian Lei (Nanomaterials)
Copper matrix composites (CMCs) synergistically reinforced with rare earth oxides (Re2O3) and TiC were prepared using a powder metallurgy process with vacuum hot-pressing and sintering technology, aiming to explore new ways to optimize the properties of composites. Through this innovative approach, we propose a new solution strategy and idea for the difficult problem of mutual constraints between electrical and mechanical properties faced by traditional dual-phase reinforced Cu-matrix composites. Meanwhile, the modulation mechanism of Re2O3 in CMCs and the electrical and mechanical properties of the composites were investigated. The compressive yield strength was improved from pure Cu (50 MPa) to TiC/Cu (159 MPa). The yield strength of Eu2O3-TiC/Cu obtained after biphasic strengthening is 213 MPa, which is 326% higher than that of pure Cu, and the ultimate compressive strength reaches 790 MPa. The conductivity was enhanced from TiC/Cu (81.4% IACS) to La2O3-TiC/Cu (87.3% IACS).